Assessing Magnesium Oxide Nanoparticles (MgONPS) for Improving Growth and Related Parameters of Chilli Plant Varieties - Parveen, Sonia; Munawar, Iqra; Khan, Khalid; Shoukat, Maham; Bilal, Khalid; Bibi, Bushra; Ikram, Iqra; Anwer, Tahseen; Anwar, Shahbaz (Indus Journal of Bioscience Research, 2025)
Nanotechnology, among the most technological advances in the field of agriculture, holds a prominent role in reshaping agriculture and food production to meet demand efficiently and cost-effectively. The use of nanotechnology in crop protection has increased resulting in high agricultural yield by the application of nanoparticles in agriculture. The main goal of nanotechnology in agriculture is to reduce the use of spread chemicals, minimize nutrient loss during fertilization, and increase crop yield through nutrient and pest management. In this research, magnesium oxide nanoparticles (MgONPS) were prepared by using the green extract of ginger and garlic under room conditions. The prepared MgONPS were characterized by Fourier transform infrared spectroscopy, ultra-violet visible spectroscopy, x-ray diffraction, and scanning electron microscopy. The UV.vis absorption showed a maximum absorption peak at 280nm, which is in the range of 260 to 280 specific for MgONPS. The XRD pattern showed the characteristic peaks and an average particle size of 20.6nm, FTIR spectrum was found in the range of 600 to 3500cm-1 determined the presence of different bonds present on the nanoparticles. These bonds absorb I.R radiation and the transition occurs from a ground vibrational state to an excited vibrational state. This research determined the assessment of synthesized MgONPS in chilli varieties. The synthesized nanoparticles were applied to chilli plants in three concentrations.  The effect of each concentration was measured compared to control. The foliar applications of the prepared MgONPS were shown to increase the plant's height, shoot length, number of leaves, number of flowers, and number of fruits compared to control.